Spreadable Jams: Implementing Social Scholarship through Remodeled Game Jam Paradigms - Saklofske, Jon (KULA)

(untitled) (University of Victoria Libraries, 2019)
Game design communities often come together during ‘Game Jams,’ open social events in which game makers creatively respond to a design provocation by generating numerous prototypes over a short period of time. Such prototypes are often discussed between participants at the end of the event, then shared with a larger public audience. This fruitful process, which encourages collaborative sharing rather than competition between participants, differs in purpose, structure and outcome from many existing models of academic scholarship and scholarly communication. Inspired by the potential of such events, this paper argues that the game jam paradigm, and more generally, ‘spaces apart,’ can be effectively adopted, adapted, and repurposed to facilitate a broader social generation and dissemination of research creation prototypes, modelling an alternative kind of scholarly making in the humanities that runs parallel to, and is as equally valued and valid as, existing publication models.